Z nepřátelské uniformy do národní armády? Nábor zajatců jako politický a etický problém zahraničního odboje - Zdenko Maršálek (Historie - Otázky - Problémy, 2020)
This paper draws attention to the range of legal, political and moral problems that the country’s representation in exile had to face in connection with the search for human resources when building up military units. Though the issue of recruiting prisoners-of-war from enemy armed forces was resolved in the field of international law, the problems arising from the clash with the national and moral ideals of the resistance movement and with the need to build a propagandistic image of the resistance were much more burdensome.